2014
DOI: 10.1002/ptr.5110
|View full text |Cite
|
Sign up to set email alerts
|

Centella asiaticain Dermatology: An Overview

Abstract: Centella asiatica is a medicinal plant that was already used as a 'panacea' 3000 years ago. The active compounds include pentacyclic triterpenes, mainly asiaticoside, madecasosside, asiatic acid and madecassic acid. We have conducted an overview to summarize current knowledge on the results of scientific in vitro and in vivo experiments focused on the improvement of the healing process of small wounds, hypertrophic scars and burns by C. asiatica. In this paper, we discuss the data on constituents, recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(158 citation statements)
references
References 30 publications
3
127
0
5
Order By: Relevance
“…24 Capryloyl glycine and iris florentine extracts are natural emollients show antibacterial activity and present a sebum-regulator effect and centella asiatica acts repairing dermal tissue, increasing collagen production, and activating blood circulation. 25 …”
Section: Methodsmentioning
confidence: 99%
“…24 Capryloyl glycine and iris florentine extracts are natural emollients show antibacterial activity and present a sebum-regulator effect and centella asiatica acts repairing dermal tissue, increasing collagen production, and activating blood circulation. 25 …”
Section: Methodsmentioning
confidence: 99%
“…C. asiatica extract is widely available in Thailand and cost effective (Taemchuay et al, 2009). Many scientific studies have researched traditional applications of C. asiatica extract (Bylka et al, 2014;Hashim, 2014). C. asiatica extract contains several bioactive compounds, including saponins, essential oils, flavone derivatives, sesquiterpenes, triterpenic acid, and triterpenic steroids (Roy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown that C. asiatica extracts exhibited antioxidant activity and UV protection effects (Hashim et al, 2011). Many beauty products are currently available that incorporate C. asiatica extracts, such as cosmetic creams, hand and body lotions, eye gel, and face mask products (Bylka et al, 2014). A previous study found that C. asiatica extract enlarged hair follicles (Jain and Dass, 2015) and inhibited the activity of 5α-reductase that causes hair loss (Jain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Centella asiatica , known by the common name Gotu kola, is a traditional herbal medicine that has been used to exert pharmacological effects in dermatology [19]. The Centella asiatica herb is used in the treatment of skin lesions such as burn wounds, excoriations, or eczema as well as in non-dermatological diseases such as diabetic complications [20], and neurodegenerative disorders [21].…”
Section: Introductionmentioning
confidence: 99%